The X-ray flare spectrum of HR 1099: the search for photopumped Ne ix line emission - Christian,DJ; Keenan,FP; Rose,SJ; Poppenhaeger,K (Publications of the Astronomical Society of the Pacific, 2025)
We present high resolution X-ray spectroscopy of the active late-type star HR 1099 obtained with the Chandra Low Energy Transmission Grating Spectrometer. A spectrum extracted from the early stages of a flare was created to search for enhanced emission due to line coincidence photopumping at X-ray wavelengths, rather than the usual optical and ultraviolet cases. Specifically, we have identified a scheme where a He-like Ne ix line at 11 Å is photopumped by He-like Na x, which predicts intensity enhancement in the Ne ix 82.76 Å transition under the high electron density and large coronal pathlength conditions found in stellar and solar flares. We previously tentatively identified a Ne ix enhancement in a solar flare spectrum, but the result was extremely uncertain. However, Ne ix 82.76 Å was detected at the 3-sigma level in the Chandra spectrum, leading to a measured Ne ix 82.76/13.45 intensity ratio of 0.21 ± 0.08. By contrast, the theoretical ratio from the CHIANTI database is at most 0.031, indicating an enhancement factor of at least 7 ± 3 for the 82.76 Å line, in agreement with the expected value of ∼7–15 from a photopumping plasma model. This confirms detection, for the first time to our knowledge, of X-ray photopumping in an astrophysical object. We note that the identification of such X-ray photopumping in other spatially unresolved sources provides in principle a new diagnostic for independently determining the sizes of their coronal regions.